Penerapan Nilai-Nilai Multikultural Dalam Membangun Sikap Dan Perilaku Menghargai Keberagaman Dan Kebinekaan Siswa - Nurlaila; Rianti, Rianti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to determine the implementation of multicultural values in order to build attitudes and behaviors that respect variety or diversity of X grade students at SMK YAPIS Santong, to know the inhibiting factors and supporting factors of the implementation of multicultural values in X grade. This study is a qualitative study that is descriptive model, by trying to describe the results of research obtained in fact. The data types used in this study are primary data and secondary data with data sources used consisting of the Head Master, vice head master for public relations and curriculum, vice head master for infrastructure and student affairs, BK teachers, parents, heads of boarding schools and X grade students with Observation data collection techniques, Interviews and Documentation. Analysis  data used in this study is deductive and Inductive. The results of this study are the implementation of multicultural values to X grade students is able to change student behavior to appreciate diversity more, and the application of multicultural values will be realized because of the routine of the school and teachers in providing an understanding of the implementation of multicultural values. The inhibiting factor in the implementation of multicultural values is the lack of student awareness, while the supporting factor is because the school is not under the affiliated of a community organization so that it will decrease the racism between one and another.